Pengaruh Promosi, Kualitas Produk dan Harga Aplikasi Terhadap Keputusan Pembelian Pada Produk Mcdonald’s (Studi Kasus Mahasiswa Universitas Islam Malang Fakultas Ekonomi dan Bisnis Angkatan 2019) - Muhammad Rijal Yusuf Izzuddin; Agus Widarko; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract In thee current era of globalization, instant and practical lifestyles are developing that affect most people in the world. Entrepreneurs introduce their businesses such as businesses in the fast food or fast food sector. Fast-food or fastfood is type offood thatis easy-topackage, easyto-serve, practiccal, prepared in-simpleway and ready to eat in a relatively quick time. This type of food is generallypopular because the-price relativelycheap, tastesgood, aand is practically-easy to carryanywhere. . The aim of this research is todetermine andanalyze theinfluence of promotions, product quality and price on purchasing decisions for McDonald's productss. This study involved 2019 students from Malang Islamic University Faculty of Economics who bought McDonald's products, but the number is unknown. The approach method uses the non-probability sampling technique, or purposive sampling, which is a sampling technique based on certain criteria with a questionnaire distributed to 80 respondents and SPSS analysis. The results of this study show that sales promotion and product quality have a positive and significant effect on purchasing decisions, while price does not have a significant effect on purchasing decisions. Keywords: Promotion, Product Quality, Price, and Purchase Decision.